Predictors of Peripheral Intravenous Phlebitis: A Study at a Regional Hospital in Indonesia - Grace Irene Viodyta Watung; Siska Sibua; Fransiskus Xaverius Dotulong; Ignatia Yohana Rembet (Media Publikasi Cendekia Indonesia, 2026)
Phlebitis is a common complication of peripheral intravenous catheter (PIVC) use that often leads to venous inflammation, pain, and significant disruption of therapy among hospitalized patients. The incidence of phlebitis in patients with PIVCs remains high, frequently exceeding the recommended threshold of ≤5%, and is associated with adverse clinical outcomes. This study aimed to analyze predictors of peripheral intravenous phlebitis among patients with intravenous fluid devices (IVFDs) at Kotamobagu Regional General Hospital. A quantitative study with a prospective cohort design was conducted in the inpatient wards of Kotamobagu Regional General Hospital from October to December 2025, involving 328 adult patients (≥18 years) with peripheral IVFDs. Pediatric patients, users of central venous catheters or PICC lines, and uncooperative patients were excluded. The results showed that 29.9% (98 out of 328 patients) had phlebitis Infusion insertion site (OR=4.32; p<0.001) was the most significant factor associated with peripheral intravenous phlebitis, followed by aseptic technique (OR=3.08; p<0.001), type of intravenous fluid (OR=2.14; p=0.003), age (OR=1.21; p=0.041), and sex (OR=1.67; p=0.018). In conclusion, prevention of phlebitis should prioritize appropriate selection of IV insertion sites, strict adherence to aseptic techniques, and careful consideration of the type of intravenous fluids, particularly in patients at higher risk based on age and sex. Non-recommended (distal) insertion sites increase the risk of phlebitis by 4.32 times compared to proximal sites